1994
DOI: 10.1161/01.hyp.24.5.556
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular autonomic modulation in essential hypertension. Effect of tilting.

Abstract: To better understand the role played by the autonomic nervous system in essential hypertension, we used autoregressive power spectrum analysis to study the noncasual oscillations in RR interval, blood pressure, and skin blood flow in 40 subjects with mild to moderate hypertension and in 25 age-matched control subjects at low frequency (index of sympathetic activity to the heart and the peripheral circulation) and high frequency, respiratory related (index of vagal tone to the heart). RR interval, respiration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 46 publications
6
85
0
1
Order By: Relevance
“…Baroreceptor sensitivity decreased as well, suggesting an increased autonomic reactivity, which is in agreement with earlier reports [25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Baroreceptor sensitivity decreased as well, suggesting an increased autonomic reactivity, which is in agreement with earlier reports [25].…”
Section: Discussionsupporting
confidence: 93%
“…Blood pressure changes reported here may not only reflect modulation of the autonomic system but vascular reactivity arising due to autonomic stimulation [25]. Moreover, spectral indices do not provide a real measure of nerve activities but only are markers of their overall interaction with target function [15].…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, our data confirmed that 0.2 Hz oscillations of BP are mechanically mediated oscillations, secondary to changes in respiration and cardiac output. 6,41,42 Moreover, our results showed that 0.2 Hz oscillations of CBFV also do not result from direct parasympathetic modulation, but are secondary to BP oscillations and their causation.…”
Section: April 2013mentioning
confidence: 50%
“…8,30 Instead, 0.2 Hz CBFV oscillations most likely arise from mechanical oscillations, secondary to BP oscillations and to respiration-induced changes in venous cardiac return and cardiac output. 6,41,42 As mentioned above, CA functions as a high-pass filter 26,27,43 that transfers BP oscillations at frequencies >0.1 Hz onto CBFV, 43 yielding secondary, mechanically induced CBFV oscillations at frequencies identical to the BP oscillations in the HF range. 6,41,42 As atropine had no effects on BP, CBFV, or on 0.2 Hz modulation of either signal, gain and phase shift between 0.2 Hz oscillations of BP and CBFV also remained unchanged.…”
Section: April 2013mentioning
confidence: 99%
“…[16,17] One study showed the evidence of poor vagal rebound after exercise in the group with H/O parental hypertension. [18] Probably, a similar mechanism of poor parasympathetic reactivation was operating in our study group too.…”
Section: Discussionmentioning
confidence: 99%